Athletic identity and discretionary effort at work - Rob Lion; Tyler Burch; Alexander R. Bolinger (Organization Management Journal (OMJ), 2024)
Purpose - The purpose of this study is to investigate whether athletic identity contributes to discretionary effort among employees. Athletic identities have long been associated with "giving 110 percent" by exerting high levels of discretionary effort. In response, a growing number of organizations have enacted recruiting programs to specifically seek out prospective employees among individuals who are likely to exhibit strong athletic identities. However, the belief that strong athletic identities will spill over to greater discretionary effort at work has not received systematic examination. Design/methodology/approach - Drawing on a field study of over 1,000 working professionals across various countries and industries, the current study explored whether athletic identity was predictive of discretionary work effort through behavioral self-control and locus of control. Bootstrapping procedures that are robust to any normality distribution violations were implemented. Findings - Results suggest that athletic identity indirectly influences employee discretionary work effort through higher behavioral self-control and a more internal locus of control. These effects were found even when controlling for actual weekly metabolic energy expenditure, age, gender and education. Originality/value - This study supports the relationship between athletic identity and discretionary effort in the workplace, mediated by greater self-regulation and internal locus of control when compared to those with weaker athletic identities. Importantly, these results were found even while controlling for actual metabolic activity, suggesting that identifying as an athlete is associated with greater internal locus of control and behavioral regulation independent of actual current physical activity. The findings suggest support for human resource practices that prioritize recruiting individuals with strong athletic identities.
Keywords: 650; Athletic identity; Discretionary work effort; Locus of control; Metabolic energy expenditure; Self-regulation